Schizencephaly and Behavioral Correlates - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The MRI appearance and neuropsychologic and speech/language evaluations in three patients with schizencephaly are described from the Department of Radiology, Michigan State University, East Lansing, MI.